STRATEGIKOMUNIKASIBIJAKMEMILIHDALAM MEMBENTUKPEMAHAMANPEMILIHPEMULATERKAIT PEMILIHANPRESIDENDANPEMILIHANUMUMTAHUN2024 - Dewi Sekartaji, Audi; Lukmantoro, Triyono; Sunarto, Sunarto (Interaksi Online, 2024)
As the majority of voters, the younger generation has not yet demonstrated readiness in voting due to a lack of knowledge about the contesting candidates and a general disinterest in politics. "Bijak Memilih" (Wise Voting) as a political education movement has formed a communication strategy to help first-time voters obtain good information during the campaign period of the 2024 presidential and general elections. By using Karl E. Weick's Organizing Process Theory and the Communication Strategy Model, this study seeks to examine the communication strategy of an organization operating within a political context. The research uses a case study design with pattern-matching techniques to analyze the data. The results show that communication strategy of Bijak Memilih includes planning, implementation, and evaluation stages for program sustainability. In the planning phase, the focus on information environment issues can be better understood through interviews and surveys conducted with various parties. The research also shows that a shared perception among members and collaborators is crucial during the implementation of the communication strategy. Bijak Memilih also introduces new models for presenting content that appeals to young people, such as delivering comprehensive information through a simple website design, using analogies in narratives, and presenting material in everyday language to make political discussions feel less rigid and intimidating. For program sustainability, evaluations are conducted by monitoring feedback from comments on social media accounts, emails, and direct messages (DMs).